Two Futures of Educational Reform: What Strategies will Improve Teaching and Learning? - Darling-Hammond, Linda (Swiss Journal of Educational Research, 2018)
This article compares the impact of recent educational reforms on school outcomes in several countries around the world. It argues that educational reforms based on conceptions of equity and capacity-building focusing on high-quality teaching and learning systems and access to good instruction for all students have proved to be more successful than educational reforms based on competition, incentives and sanctions.